The signage design consideration for wayfinding in UNESCO heritage site of Melaka - Noor Roziana Abdul Rahim (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
Melaka UNESCO heritage sites is recorded as one of the most visited places in Malaysia in 2015. These sites are significant to tourists, thus are equipped with public facilities. An effective signage design around these sites must be put into careful consideration to ease the tourists' wayfinding. Several studies on signage in heritage site, tourism, user experience, signage and wayfinding have been conducted, however they are not focused on Melaka UNESCO heritage sites. There is a gap on the signage in heritage site, tourism, user experience, signage and wayfinding around UNESCO heritage site of Melaka areas. Therefore, this study focuses on analyzing the signage design consideration for wayfinding in UNESCO heritage sites of Melaka. The objectives of this study are to identify the content and composition in existing signage of heritage sites, to determine the level of usage of signage universal design guideline in existing signage in UNESCO heritage sites of Melaka and to develop signage design consideration for wayfinding in UNESCO heritage sites of Melaka. The data was collected through the site inventory, profiling, checklist, pilot survey, main survey and video taking in the UNESCO heritage sites of Melaka. The findings from this research indicate that most of the signage in the heritage sites are not effective due to the unsuitable location and ineffective design. Some of the existing signages are following Universal Design Guideline in content and composition except for the hardware system which include shape, size, eye level and clarity. Thus, it is suggested that the signages should be sensitively located, scaled and detailed so as not to obscure ambiguous or distract the tourists from historical objects. Apart from that, signages with good functional attributes and suitable location will make the journey of the tourists who are visiting the UNESCO site of Melaka enjoyable and less time consuming. In conclusion, this research contributes to the field of tourism by providing a design consideration for the signage that can be adapted by the local authority for designing signage for UNESCO heritage site in the future.